2010
DOI: 10.1088/0004-637x/723/2/1119
|View full text |Cite
|
Sign up to set email alerts
|

ON THE POPULATIONS OF RADIO GALAXIES WITH EXTENDED MORPHOLOGY ATz< 0.3

Abstract: Extended extragalactic radio sources have traditionally been classified into Fanaroff & Riley (FR) I and II types, based on the ratio r s of the separation S between the brightest regions on either sides of the host galaxy and the total size T of the radio source (r s ≡ S/T ). In this paper, we examine the distribution of various physical properties as a function of r s of 1040 luminous (L L * ) extended radio galaxies (RGs) at z < 0.3 selected with well-defined criteria from the SDSS, NVSS, and FIRST surveys.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 66 publications
(87 reference statements)
5
53
2
Order By: Relevance
“…Similar to the results of Best (2009) and Lin et al (2010), we found that while there may be a general trend for FR I sources to reside below the line proposed by Ledlow & Owen (1996), it is by no means an absolute separation. Specifically, we found that for the visual-bent sample, 81% of the sources we visually identified as FR I sources are also FR I sources according to the criteria of Ledlow & Owen (1996).…”
Section: Determining Radio Power and Fr Morphologysupporting
confidence: 89%
“…Similar to the results of Best (2009) and Lin et al (2010), we found that while there may be a general trend for FR I sources to reside below the line proposed by Ledlow & Owen (1996), it is by no means an absolute separation. Specifically, we found that for the visual-bent sample, 81% of the sources we visually identified as FR I sources are also FR I sources according to the criteria of Ledlow & Owen (1996).…”
Section: Determining Radio Power and Fr Morphologysupporting
confidence: 89%
“…Indeed, in using Monte Carlo simulations to test whether observed samples of radio galaxies can be random selections of elliptical galaxies, Scarpa & Urry (2001) found that the two FR classes are hosted by ellipticals extracted from the same population. Also, the Owen-Ledlow diagrams of radio samples in later studies are not found to be as sharply divided between the two classes as originally found and there is non-insignificant number of FR-IIs below the canonical dividing line (Ledlow & Owen 1996;Lin et al 2010). These below-line FR-IIs, which are also found to be compact in physical size, have been speculated as being FR-IIs that are likely to evolve into FR-Is as their low-power jets get frustrated in interactions with the interstellar medium (ISM) of the host galaxy (Kaiser & Best 2007).…”
Section: The Owen-ledlow Diagrammentioning
confidence: 55%
“…There is also uncertainty surrounding the exact physical mechanism that turns energy from accreted material into well-collimated jets, and why some systems show no jets at all. Lin et al (2010) find that different radio morphologies are more dependent on the accretion rate than the galaxy's structure, with highlyextended, lobe-dominated radio galaxies having higher accretion rates than their less-extended counterparts. Furthermore, the work of Fernandes et al (2011) indicates that there is a minimum accretion rate for a given radio power, suggesting that there is a maximum efficiency with which the black hole is able to produce jets from infalling material.…”
Section: Radio Emission From Agnmentioning
confidence: 88%